Pengelolaan Limbah Kulit Buah Naga Menjadi Saus Untuk Mendukung Ketahanan Pangan di Desa Jaten, Karanganyar - Utami, Bekti Wahyu; Saputri, Anggi Dwi; Damayanti, Citra; Adha, Fais Fadhila Nur; Nadia, Jasmin; Syaputra, Muhammad Ramadhan; Yunus, Muhammad; Kusumahandayani, Putri; Vitria, Salma; Firdaus, Salsabila; Hasanah, Uswatun Nur (Karunia: Jurnal Hasil Pengabdian Masyarakat Indonesia, 2025)
The UNS Community Service Program (KKN) Batch 68 was conducted from July to August 2025 in Jaten Village, Karanganyar Regency, Central Java. This program focused on educating the community about the utilization of organic waste, particularly dragon fruit (Hylocereus spp.) peel, which is generally underutilized. Dragon fruit peel has the potential to be developed into functional food products as it contains fiber, vitamins, and pectin. Through the “Dragon Fruit Peel Waste Management into Sauce” workshop, participants were provided with knowledge and skills to process organic waste into value-added products while supporting household food security. The implementation methods included counseling, demonstrations, and hands-on practice. The results showed an increase in community understanding of food waste management, improved skills in processing dragon fruit peel into sauce, and the establishment of communication networks among village cadres for program sustainability. This innovation also holds potential to be developed into micro-enterprises in the healthy food sector.